How is the Impact of the Corporate Governance Mechanism on IPO Underpricing? (Empirical Study on Companies conducting IPOs on the Indonesia Stock Exchange 2010-2019) - Kiki Satria Hutama Putra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study is to examine how the influence of corporate governance mechanisms on the level of underpricing of IPO companies in Indonesia. This study examines 301 company IPOs during the period 2010 to 2019 using secondary data collected through annual reports and company IPO prospectus on the Indonesia Stock Exchange. Sampling was done by purposive sampling technique with a final sample of 72 companies. Multiple linear regression analysis was used to examine the impact of corporate governance mechanisms on IPO underpricing. The results showed that female directors had a significant effect on underpricing the company's IPO. while the board of commissioners, the independence of the board of commissioners, the board of directors, the age of the board of directors, the board of the audit committee and the age of the company have no significant effect on the underpricing of the company's IPO.